2011
DOI: 10.1016/s1734-1140(11)70414-5
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin affects the tissue concentration of hydrogen sulfide inmouse kidneys and other organs*

Abstract: Hydrogen sulfide (H2S) is a crucial co-modulator of cardiovascular, nervous, digestive and excretory systems function. The pleiotropic action of atorvastatin exceeds simple 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibition and involves multiple biological mechanisms. This study assesses the influence of atorvastatin on the H2S tissue concentration in mouse brain, liver, heart and kidney. Twenty-four female CBA strain mice received an intraperitoneal injection. The mice were given one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Statins are shown to increase H 2 S level by inhibiting its metabolism [47]. Administration of SQR inhibitors can potentially inhibit H 2 S breakdown [48].…”
Section: Discussionmentioning
confidence: 99%
“…Statins are shown to increase H 2 S level by inhibiting its metabolism [47]. Administration of SQR inhibitors can potentially inhibit H 2 S breakdown [48].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous H 2 S in mammalian cells is known to be regulated by enzyme pathways such as cystathionine gamma lyase (CSE) and cystathionine beta synthase (CBS) . Statins, known as a class of cholesterol‐lowering drugs, could up‐regulate the CSE expression, and subsequently elevate the H 2 S generation in cells . Gu et al.…”
Section: Bodipy‐based Probes For Biothiolsmentioning
confidence: 99%
“…Clearly these are unrealistically high, however, they are nevertheless suggestive of drug perturbation of intracellular sulfide. Using the same methods, this group also observed that the statin, atorvastatin, substantially increased kidney H 2 S and slightly increased H 2 S in brain heart and liver [134]. Wójcicka et al [135] also observed that atorvastatin increased H 2 S production in perivascular adipose tissue by producing coenzyme Q 9 deficiency and thereby inhibiting mitochondrial oxidation.…”
Section: Other Questions Remaining and Future Directionsmentioning
confidence: 97%